Penerapan Media Audiovisual (Video) Untuk Meningkatkan Minat Belajar Siswa Pada Pembelajaran PAI di SMK Muhammadiyah 5 Jember - Zanah, Siti Nur Miftahul; Rofiq, M. Nafiur (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
The purpose of this study is to comprehend how Islamic Religious Education (PAI) learning activities at SMK Muhammadiyah 5 Jember use audiovisual media, especially videos, and to evaluate how effectively it works as a tactic to boost student interest and engagement. Using a qualitative approach and field research method, the findings demonstrated that using videos significantly improves students' comprehension and retention of the material, particularly when the videos' content is created by the students themselves and is connected to real-world experiences. Learning becomes more dynamic and significant when students participate in the video-making process. The school, through the Vice Principal for Curriculum, stated that the use of audiovisual media is in line with the implementation of the technology-based and student-oriented Independent Curriculum. From interviews with students, it is known that the use of videos makes the learning process more interesting, fun, relevant and able to increase their learning motivation. Therefore, audiovisual media is proven to be able to improve the quality of PAI learning and is recommended to be applied to other subjects as well.